Implementasi Metode Waterfall Pada Sistem Informasi Inventaris Barang Berbasis Web Di Hotel Grand Edge Semarang - Widodo, Tulus Suryo; Prihati, Yani; Gondohanindijo, Jutono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
A company asset, inventory management must always be monitored for its existence and condition. Inventory management of a company is very important. The stages of the waterfall software development method are used as the basis for the structure of requirements analysis, design, implementation, and system testing. Employee input data, item input data, and purchase input data are some parts of the designed information system. By choosing an efficient Rapid Application Development (RAD) approach, a Web-based Goods Inventory Information System was developed to solve the problem of errors and data duplication. The research methodology consists of observation, interviews, literature research. The purpose of this research is to design a web-based inventory information system to help manage inventory data at Grand Edge Hotel Semarang.